Insight on patient profile undergoing caesarean delivery: a hospital based study in Karnali Academy of Health Sciences - Basnyat, Subi; Shah, Rajiv; Baral, Gehanath; Khapung, Robin; Khadka, Shailaja; Silwal, Shirish; Thapa, Rubi (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Cesarean section (CS) rates are rising globally, often exceeding World Health Organization recommendations. While well-documented in urban centers, data from remote, resource-limited regions such as Nepal’s Karnali Province are scarce. This study aims to determine the key maternal characteristics and clinical indications for CS at a tertiary hospital in a remote setting.Methods: This was a retrospective, cross-sectional study of all deliveries at Karnali Academy of Health Sciences between June 2023 and June 2024. Data on maternal demographics, obstetric history, and CS indications were collected from hospital maternity records. Descriptive statistics were used to analyze the data.Results: Among 801 deliveries, 180 were cesarean sections, yielding a CS rate of 22.5%. The mean maternal age was 24.75±4.92 years, and nulliparous women constituted the largest group (42.8%). Most CSs were emergency procedures (84%). The leading indications were previous CS (16.1%), breech presentation (13.9%), meconium-stained liquor (10.6%), and fetal distress (10.6%). Robson classification analysis identified women with a previous CS (Group 5) as the largest contributor to the overall rate (23.3%).Conclusion: The CS rate in this remote Nepalese hospital is elevated. The high proportion of emergency procedures and the prominence of previous CS as a primary indication highlight critical areas for intervention. To optimize CS use, targeted strategies such as promoting vaginal birth after cesarean and strengthening standardized intrapartum monitoring are urgently needed.